2012
DOI: 10.1111/j.1464-410x.2012.11415.x
|View full text |Cite
|
Sign up to set email alerts
|

Safety of no bowel preparation before ileal urinary diversion

Abstract: Study Type – Harm (case series)Level of Evidence 4What's known on the subject? and What does the study add?Recent studies show no advantage of bowel preparation before ileal urinary diversion and that avoidance of bowel preparation led to early restoration of intestinal function and shorter hospital stay. However, this was not tested in a prospective comparison.The current study is a prospective comparison to test for the safety of omitting bowel preparation before ileal urinary diversion. This study also exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 14 publications
0
10
0
4
Order By: Relevance
“…The test for heterogeneity among studies was not statistically significant, so the fixed-effects model was used for all comparisons. All trials reported the rate of wound infection [10,11,12,13,22,23,24]. The pooled estimate indicated that the outcome measure was not affected by the use of MBP (OR 0.84; 95% CI 0.41-1.75; p = 0.65).…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…The test for heterogeneity among studies was not statistically significant, so the fixed-effects model was used for all comparisons. All trials reported the rate of wound infection [10,11,12,13,22,23,24]. The pooled estimate indicated that the outcome measure was not affected by the use of MBP (OR 0.84; 95% CI 0.41-1.75; p = 0.65).…”
Section: Resultsmentioning
confidence: 85%
“…Of these, 1 study lacked a control group [18], 2 studies made an inappropriate comparison [19,20], and 1 study focused on old people [21]; these studies were all excluded. In the end, 7 articles were identified for inclusion (two RCTs and five cohort studies) [10,11,12,13,22,23,24]. The overall risk of bias was unclear in 2 RCTs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Важность предоперационного консультирования пациентов от-носительно ведения в режиме fast track подчеркнута неоднократно [15,16]. Тем не менее на сегодняшний день нет ни одного исследования его роли среди онко-урологических пациентов.…”
Section: Discussionunclassified
“…В ряде работ пока-зано, что в колоректальной хирургии она приводит к электролитному дисбалансу, психологическому стрессу и продолжительным нарушениям перисталь-тики [20]. Многие авторы экстраполировали данные работ в колоректальной хирургии в онкоурологиче-скую практику [21], сосредоточившись, тем не менее, на цистэктомии -вмешательстве, выполняемом с ис-пользованием сегмента кишки. Наши результаты под-твердили отсутствие влияния подготовки кишечника на частоту развития осложнений (см.…”
Section: Discussionunclassified